Human depreciation accounting and the emergence of industrial pensions. Issue 2 (16th February 2015) - Himick, Darlene
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate how the accounting notion of "human depreciation" helped the defined benefit pension plan emerge as the dominant means of dealing with an aging workforce in the first half of twentieth century USA. Design/methodology/approach – The study examines historical material to identify the intersection of several different practices and knowledges that came together in the early decades of the 1900s to permit human depreciation in 1949 to be used to formally link aging employees to their employers. Findings – In the early part of the twentieth century, humans and machines were constructed as parts of a single productive system, human traits were studied in order to increase their machine-like capacities, in the hope of creating a more efficient industrial economy. At the same time, fatigue associated with this industrial nation was constructing the older worker as subject to decline, hence opening the door to a linkage to physical and economic depreciation. Social implications – Reveals that the language of accounting can be utilized by non-accountants and outside organizational boundaries to effect public policy and play a constitutive role. Thus, who is able to use accounting conventions is important in understanding how accounting shapes social settings. Originality/value – "Human depreciation", used by the Steel Industry Board in 1949 to assign responsibility to employers for the depreciation of their human assets, has been left unexamined despite being cited as one of the greatest contributors to the growth of industrial pensions in the USA. The study examines accounting as an interface among and between the organizational and "non-accounting" spheres.